Intergenerational Learning Processes of Traditional Medicinal Knowledge and Socio-Spatial Transformation Dynamics - Ouma, Anne (Frontiers in Sociology, 2022)
The transfer of Traditional knowledge to new generations of traditional medicinal practitioners takes place through place-based intergenerational learning processes, which are increasingly challenged by intensified rural-urban migrations and accelerating biodiversity loss. Research on traditional medicinal knowledge (TMK) has mainly focused on medicinal properties of different plant species while social, economic and locational aspects of TMK learning processes have received less attention. The purpose of this article is to contribute to the research field by examining how learning processes of TMK are affected by on-going socio-spatial transformations in rural and urban parts of Eastern Lake Victoria region. Urbanisation, migration and increased commercialisation of traditional medicinal products are transforming learning processes of TMK and affect the ways traditional practitioners are able to transfer TMK to new generation of practitioners. Based on in-depth interviews and focus group discussions with male and female traditional practitioners aged between 30 and 95 years old from rural and urban settings in Mwanza (Tanzania) and Nyanza (Kenya) in the Lake Victoria Region. The Paper analyses the role of socio-spatial and migration dynamics on major intergenerational forms of learning of TMK (learning in place; being sent; ritual places); health knowledge diffusion and interactions between TMK and formal health systems. Despite some major challenges to the continuity of TMK learning due to increased migration identified by the traditional practitioners, many also saw emerging roles for TMK in primary health care for sustaining livelihoods for the younger generations of men and women in this region.